2010
DOI: 10.1007/s00240-010-0275-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic urinary stone surgery: an updated evidence-based review

Abstract: The treatment of urinary lithiasis has been revolutionized during the last three decades. Minimally invasive therapies in the form of endoscopic surgery in companion with the advent of shock wave lithotripsy have diminished the role of open stone surgery. Laparoscopy, another minimally invasive treatment, is continuously gaining place in the treatment of urinary stones, mainly replacing open surgery. We have tried to identify the level of the evidence and grade of recommendation, according to the evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…The European Association of Urology (EAU) Guidelines on urolithiasis of 2013 summarized the indications for laparoscopy, which include stones in caliceal diverticula, stones in anomalous and/or ectopic kidneys, and stones associated with UPJO when other minimally invasive procedures are not indicated or have failed 5. In a systematic review, Skolarikos et al determined that the highest level of evidence supporting the role of laparoscopy in the management of lithiasis was IIa for laparoscopic ureterolithotomy 6. However, Lusuardi and Janetschek suggested that laparoscopy can be offered as first-choice treatment when anatomic abnormalities are involved, such as UPJO 7.…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology (EAU) Guidelines on urolithiasis of 2013 summarized the indications for laparoscopy, which include stones in caliceal diverticula, stones in anomalous and/or ectopic kidneys, and stones associated with UPJO when other minimally invasive procedures are not indicated or have failed 5. In a systematic review, Skolarikos et al determined that the highest level of evidence supporting the role of laparoscopy in the management of lithiasis was IIa for laparoscopic ureterolithotomy 6. However, Lusuardi and Janetschek suggested that laparoscopy can be offered as first-choice treatment when anatomic abnormalities are involved, such as UPJO 7.…”
Section: Discussionmentioning
confidence: 99%
“…Keeley et al [15] reported the advantages of transperitoneal laparoscopic ureterolithotomy in which there is high probability of removing the entire stone burden in one procedure. In an evidence-based review by Skolarikos et al [16], the highest level of evidence (IIa) was found for laparoscopic ureterolithotomy supporting the laparoscopic approach of stone extraction and mostly recommended (grade B) for large impacted stones or when endoscopic techniques have failed. Due to scarcity of complex and large stones nowadays, there are few studies which actually compared the laproscopic and open techniques of ureterlithotomy in prospective design and most of the previous laparoscopic studies are unrandomized and not actually comparative [17,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The highest level of evidence was IIa for laparoscopic ureterolithotomy and recommended (grade B) for large impacted ureteral stones or when endoscopic ureterolithotripsy or shock wave lithotripsy (SWL) has failed [5].…”
Section: Introductionmentioning
confidence: 99%